2007
DOI: 10.1111/j.1365-2133.2007.08036.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the secretion mechanism of the sebaceous gland using three-dimensional reconstruction to examine the morphological relationship between the sebaceous gland and the arrector pili muscle in the follicular unit

Abstract: We propose that the concave part of the AP muscle pushes up the basal portion of the sebaceous lobule between the HFs and AP muscle during AP muscle contraction and hair erection. In addition, the sebaceous lobule located at the counter-angular position is squeezed by the HF during AP muscle relaxation and hair repositioning. Combined with the previous mechanism of SG secretion, this newly established mechanism based on the 3D structure of the FU will improve our understanding of AP muscle function and SG secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…In general, the arrector pili muscles of body hairs comprise smooth muscle and connect the follicle to the basement membrane of the epidermal-dermal junction [Song et al, 2005[Song et al, , 2006[Song et al, , 2008. In contrast, the vibrissal capsular muscle originates from the deeply located facial skeletal muscles, and its course and morphology are very different from those of other arrector pili muscles.…”
Section: Functional Location Of Vibrissal Capsular Musclementioning
confidence: 99%
“…In general, the arrector pili muscles of body hairs comprise smooth muscle and connect the follicle to the basement membrane of the epidermal-dermal junction [Song et al, 2005[Song et al, , 2006[Song et al, , 2008. In contrast, the vibrissal capsular muscle originates from the deeply located facial skeletal muscles, and its course and morphology are very different from those of other arrector pili muscles.…”
Section: Functional Location Of Vibrissal Capsular Musclementioning
confidence: 99%
“…The structure of the arrector pili muscle has been reported in the literature with regard to hair [10], dermatology [4, 32], anatomy [28], and zoology [1], although many of the details are still controversial. The morphology of the distal ends of the muscle has been studied by several investigators [2, 2123], and 3D structure models have recently been presented [26, 27]. Although the distal ends of the arrector pili muscle are drawn as if they adhere closely to the basement membrane beneath the layer of the skin epidermis in most literatures, it is notable that the authors of Gray’s anatomy [28] as well as some other papers [22, 23] have illustrated them in a way that shows they are not attached directly to the basement membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies were shown to be the best method of investigating hair follicles [Headington, 1984], with three-dimensional (3-D) reconstruction based on serial cross sections, which reveal the actual microstructure and function of hair follicles and their appendages [Song et al, 2005[Song et al, , 2006[Song et al, , 2007. Moreover, our previous 3-D reconstruction study showed that the structure of the vibrissal follicle-sinus complex differed from previous reports [Kim et al, 2011].…”
Section: Introductionmentioning
confidence: 56%